2020
DOI: 10.3390/jcm9010200
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Nitric Oxide in Chronic Rhinosinusitis with or without Nasal Polyps: A Systematic Review with Meta-Analysis

Abstract: Background and Aims: There has been a recent growing interest in the role of nasal nitric oxide (nNO) as a biomarker for osteomeatal complex obstruction in paranasal sinus diseases. By using meta-analysis, we systematically reviewed the literature to establish the possible link between nNO concentration and chronic rhinosinusitis with nasal polyps (CRSwNP) or without (CRSsNP). Methods: We systematically searched the EMBASE, PubMed, Scopus, and Web of Science databases for related studies. Differences between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…In brief, eosinophilic airway inflammation derives from the activation of mast cells and antigen-specific T helper 2 cells, with the concomitant production of cytokines, such as interleukin (IL)-4, IL-5 and IL-13 [ 10 ]. Their release regulates the expression of the inducible isoform of NO synthase (iNOS), thus determining an increased NO production in an allergic environment [ 11 ]. This implies that FeNO assessment may be able to accurately predict eosinophilic airway inflammation - a peripheral trigger of cough reflex with a good ICS response - in a rapid, non-demanding and cost-effective manner [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, eosinophilic airway inflammation derives from the activation of mast cells and antigen-specific T helper 2 cells, with the concomitant production of cytokines, such as interleukin (IL)-4, IL-5 and IL-13 [ 10 ]. Their release regulates the expression of the inducible isoform of NO synthase (iNOS), thus determining an increased NO production in an allergic environment [ 11 ]. This implies that FeNO assessment may be able to accurately predict eosinophilic airway inflammation - a peripheral trigger of cough reflex with a good ICS response - in a rapid, non-demanding and cost-effective manner [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Past observation that the nitric oxide (NO) concentration in exhaled air generally increases in chronic inflammatory airway diseases [ 10 , 11 ] has led the European Respiratory Society (ERS) and the American Thoracic Society (ATS) to agree on highly standardised procedures to measure fractional exhaled NO (FeNO) [ 12–14 ]. Thus, FeNO has become an important non-invasive support to monitor compliance and efficacy of steroids in chronic airway diseases, especially asthma [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Frendø et al [28] found that in patients with CRSwNP, nNO levels were significantly lower than those in the controls. A meta-analysis by Ambrosino et al [29] also revealed that compared with healthy controls, CRSwNP patients showed significantly lower nNO levels. Similar to previous research, our results also showed that patients with CRSwNP had lower nNO levels compared with the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Negative correlations have been observed between nasal NO levels and the severity of sinus infection, as indicated by computed tomography (CT) scores or nasal polyp scores [ 59 , 112 , 115 , 116 , 117 ]. Ambrosino et al recently performed a systematic review to investigate the possible link between the nasal NO concentration and CRS phenotypes, and they reported that CRSwNP patients showed significantly lower nasal NO values compared to those of both healthy controls and CRSsNP patients, based on 23 selected articles [ 118 ]. Interestingly, the observed difference in nasal NO levels was related to the flow rate of the nasal aspiration, with the difference between cases and control subjects being more prominent when higher aspiration flows were used.…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%
“…On the other hand, it remains controversial whether a link exists between nasal NO levels and the severity of ECRS, due (probably) to the multifunctional roles of NO [ 118 ]. A recent study reported that nasal NO levels determined by subtracting the nasal FeNO level from the oral FeNO level were significantly lower in the CRS group (both ECRS and non-ECRS) than in the control group, with the ECRS group’s difference being more prominent [ 112 ].…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%